No mutations of FecB and FecGH in Iranian Lory sheep - Zaynab Shafieiyan; Ghodratollah Mohammadi; Abbas Jolodarzadeh; Sara Amiri (Veterinary Research Forum, 2014)
The Booroola fecundity gene (FecB) and growth differentiation factor 9 (GDF9) gene belong to the transforming growth factor β (TGF-β) superfamily. The mutations of these genes have additive effects on the prolificacy in sheep. The aim of the present study was to determine the possible mutations of FecB and FecGH genes in Lory sheep breed of the Lorestan province, Iran. Sixty blood samples were collected and DNA was extracted from whole fresh blood. For detection of FecB and FecGH mutations, the PCR products were incubated with AvaII and DdeI restricted enzymes. Based on the results we did not find the FecB and FecGH mutations in this sheep breed population, so these mutations cannot the cause of the high prolificacy of Lory sheep breed and more study are needed to determine the genetic or environmental causes of high prolificacy of this sheep breed.